2007
DOI: 10.1128/aem.01748-06
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Astrovirus from Water and Sewage Treatment Plants, Evaluated by a Competitive Reverse Transcription-PCR

Abstract: Quantification of human astrovirus genogroups A and B was undertaken with sewage and water samples, collected from the Greater Cairo area in Egypt from November 1998 to October 1999, by a competitive reverse transcription (RT)-PCR with an internal control. The number of RNA copies of genogroup A/liter in quantifiable samples ranged from 3.4 × 103 to 5.6 × 106 in raw sewage and from 3.4 × 103 to 1.1 × 104 in treated effluents, while the number of infectious units per liter in these samples as determined by cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 21 publications
(8 reference statements)
2
30
1
3
Order By: Relevance
“…It may be because of the very low number of the viral genome. Infectious units of enteric viruses are usually 2-3 log 10 lower than genome copies in Egyptian sewage or Nile water samples (El-Senousy et al 2007;El-Senousy et al 2013a). Another reason may be the low sensitivity of MA104 cell line to the infectivity of rotavirus group C. Rotavirus group A genome copy numbers in the final chlorinated sewage effluents ranged from 9 9 10 to 9 9 10 3 genome copies/l, while the number of infectious units in the same samples ranged from 1 9 10 to 6 9 10 infectious units/l.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It may be because of the very low number of the viral genome. Infectious units of enteric viruses are usually 2-3 log 10 lower than genome copies in Egyptian sewage or Nile water samples (El-Senousy et al 2007;El-Senousy et al 2013a). Another reason may be the low sensitivity of MA104 cell line to the infectivity of rotavirus group C. Rotavirus group A genome copy numbers in the final chlorinated sewage effluents ranged from 9 9 10 to 9 9 10 3 genome copies/l, while the number of infectious units in the same samples ranged from 1 9 10 to 6 9 10 infectious units/l.…”
Section: Discussionmentioning
confidence: 97%
“…Rotavirus CC-RT-PCR assay was performed according to Abad et al (1997), El-Senousy et al (2007), and Ghazy et al (2008). The assay was performed on suspensions of infected MA104 cells.…”
Section: Cell Culture Rt-pcr (Cc-rt-pcr) For Quantification Of Infectmentioning
confidence: 99%
“…Enzyme immunoassay (EIA) for norovirus and astrovirus (IDEIA TM Norovirus, IDEIA TM Astrovirus and DakoCytomation), rotavirus and enteric adenovirus (IDV Rotavirus-96, IDV Adenovirus-96 and Izasa) were performed on stool specimens. Additionally, reverse transcriptase-polymerase chain reaction (RT-PCR) detection was performed as previously described (Allard et al, 1992;Guix et al, 2002;Morsy El-Senousy et al, 2007;Vinje and Koopmans, 1996;Villena et al, 2003). Norovirus genotyping was performed by sequencing the amplimers obtained with the JV12/JV13 pair of primers.…”
Section: Methodsmentioning
confidence: 99%
“…A difference in the stability of different AstVs in the environment has been suggested. For example, Morsy El-Senousy et al (42) reported that genogroup B classic HAstVs (types 6 and 7) are more resistant to wastewater treatments than other classic HAstV genogroups. In our current study, however, this genogroup was not detected in wastewater (Fig.…”
Section: Discussionmentioning
confidence: 99%